PENGARUH USIA PERUSAHAAN, KUALITAS AUDIT DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Reza Muhammad Rizqi (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This study aims to examine the impact of certain variables, such as Company Age, Audit Quality and Profitability, on Earnings Management practices in companies engaged in the Trading sector listed on the Indonesian Stock Exchange during the 2018-2022 period. This study uses information obtained from the financial statements of companies in the trading sector which are listed on the Indonesia Stock Exchange. A total of 18 companies were selected as research samples for the 2018-2022 period. To perform data analysis, SPSS version 25 software was used. The results of this study indicate that firm age has a positive and significant effect on earnings management, audit quality variable has a negative effect on earnings management, and profitability variable has a positive and significant effect on earnings management. The findings in this study also explain company age, audit quality, and profitability simultaneously or jointly have a significant effect on the dependent variable, namely earnings management in trading sector companies in 2018-2022